Modelling ventilation and convective heat transfer in deeply buried underground tunnels based on boundary layer theory - Guo Jinnan; Li Angui (E3S Web of Conferences, 2022)
Underground traffic tunnels serve as the entry and exit buildings for underground spaces. Most of the ventilation and air-conditioning systems in underground spaces rely on traffic tunnels for cooling or preheating to save energy. The temperature distribution of traffic tunnels has always attracted the attention of researchers. In this study, a heat transfer model of a traffic tunnel was established based on energy conservation and boundary layer theory, and the field test was carried out. The calculation model provided in this study was in good agreement with the field measurement results. It is found that the dimensionless air temperature of the traffic tunnel decays exponentially along the tunnel at the same time. The air temperature in the traffic tunnel fluctuates with time, and the simple harmonic fluctuation decreases along the tunnel. In summer, the air temperature decreases and increases exponentially along the tunnel during the day and night, respectively. In this study, a heat transfer model for calculating the temperature distribution of underground traffic tunnels was theoretically established, which provided an important theoretical support for underground traffic tunnels as natural air conditioners. The establishment of heat transfer model of underground traffic tunnel has significant economic and environmental benefits.